2022
DOI: 10.1111/and.14412
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ejaculation in men with depressive disorders

Abstract: Delayed ejaculation (DE) is one of the most difficult disorders to diagnose from male sexual dysfunctions. It is characterized by a significant ejaculation delay or even an inability to achieve ejaculation (AE). It is a disorder that affects men, but it can also have a secondary effect on their wives/partners and possibly their ability to fertilize. The 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM) describes this sexual disorder as ejaculation which is delayed or absent in at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…Long-term high psychological distress levels tend to produce more negative emotions, which may reduce men's sexual desire by stimulating the secretion of prolactin (Wang and Xue, 2021). Consistent with a previous study (Junsheng et al, 2013), the present study indicated that psychological distress could predicate the occurrence of TEF, the reason was that distress is thought relevant to sexual disorders or elevated prolactin levels (Fiala et al, 2022). Thus, applying the intervention such as yoga therapy and self-administered mindfulness reduced the psychological distress (Bai et al, 2019;Dumbala et al, 2020), which was a critical benefit for patients with assisted reproduction.…”
Section: Discussionsupporting
confidence: 87%
“…Long-term high psychological distress levels tend to produce more negative emotions, which may reduce men's sexual desire by stimulating the secretion of prolactin (Wang and Xue, 2021). Consistent with a previous study (Junsheng et al, 2013), the present study indicated that psychological distress could predicate the occurrence of TEF, the reason was that distress is thought relevant to sexual disorders or elevated prolactin levels (Fiala et al, 2022). Thus, applying the intervention such as yoga therapy and self-administered mindfulness reduced the psychological distress (Bai et al, 2019;Dumbala et al, 2020), which was a critical benefit for patients with assisted reproduction.…”
Section: Discussionsupporting
confidence: 87%